Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T15:17:43+01:00
2(x+3)=2x+6
5(3x-1)=15x-5
(-4)*(2a-b)=-8a+4b
-2(-4b+3)=8b+6
(a+b)*(-4)=-4a-4b
(4-5x+6y)*3=12-15x+18y
-3(3x-2)=-9x+6
-1(3xiy+2)=-3xiy-2
(6x-2y):2=3x-y
(-3a-1,5):(-3)=a+0,5
(2,4a-1,6b):0,8=3a-2b
(4u-6v):(-1,5)=-2,(6)u+4v
2010-03-17T15:20:33+01:00
2(x+3)=2x+6
5(3x-1)=15x-5
(-4)*(2a-b)=-8a+4b
-2(-4b+3)=8b-6

-1(3xiy+2)=-3xiy-2
(6x-2y):2=3x-y
(-3a-1,5):(-3)=a+0,5
(2,4a-1,6b):0,8=0,3a-0,2b
2010-03-17T15:22:08+01:00

2(x+3)=2x+6
5(3x-1)=15x-5
(-4)*(2a-b)=-8a+4b
-2(-4b+3)=8b-6
(a+b)*(-4)+(4-5x+6y)*3-3(3x-2)=-a-b+12-15x+18y-9x+6=18-24x+18y-a-b
-1(3xiy+2)=-3xy-2
(6x-2y):2=3x-y
(-3a-1,5):(-3)=1a+0,5
(2,4a-1,6b):0,8=3a-2b